The beast within: H.G. Wells, The Island of Doctor Moreau, and human evolution in the mid‐1890s. (9th October 2014) - Mcnabb, John; Donovan, Stephen K.; Stringer, Christopher B.
<x xml:space="preserve">Abstract</x> H.G. Wells' novels The Time Machine and The Island of Doctor Moreau were both concerned with the evolutionary destiny of mankind and what it meant to be human, both important areas of discussion for Victorian natural science in the 1890s. In this essay, I set these two works in their broader scientific context and explore some of the then contemporary influences on them drawn from the emerging disciplines of archaeology and anthropology. Wells was a student of T.H. Huxley whose influence on his own emerging views on human evolution is clear. While most scientists and the lay‐public accepted the reality of evolution by the 1890s, and the natural origins of the human species, fear of the implications of our 'primitive' heritage pervaded popular and scientific works. Wells bridged that gap with an uncompromising outlook delivered to the public as scientific truth delivered through short stories, novels and scientific journalism. Copyright © 2014 John Wiley & Sons, Ltd.